PRICE EFFECT ON CONSUMER BUYING INTEREST WITH CUSTOMER SATISFACTION AS INTERVENING VARIABLES (Case Study of Community Users of Health Facilities in the United States) - Arnaud Costinot; Stephen Martin (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2021)
This study aims to determine“The Influence of Price on Consumer Purchase Interest with Consumer Satisfaction as an Intervening Variable (Case Study of Community Users of Health Facilities in the United States)”. the results of this study indicate that 1)it can be seen that tcount (3.128) > ttable (1.667), likewise with a significance value of 0.00 <0.05, it can be concluded that the first hypothesis is accepted, meaning that the Price variable(X) positive and significant effecton Customer Satisfaction (Y1). 2) it can be seen that tcount (1.766) > ttable (1.667), and a significance value of 0.00 <0.05, it can be concluded that the second hypothesis is accepted, meaning that the price(X) positive and significant effecton Buying Interest (Y2). 3) it can be seen that tcount (6.987) > ttable (1.667), and the significance value is 0.00 <0.05, it can be concluded that the third hypothesis is accepted, meaning Customer Satisfaction (Y1)influentialpositive andsignificanton Buying Interest (Y2). 4) the direct effect of variable X on variable Y2 is 0.162. While the indirect effect through the Y1 variable is 0.357 x 0.642 = 0.2291, the calculation results obtained show that the indirect effect through the Y1 variable is greater than the direct effect on the Y2 variable.